2014
DOI: 10.1016/j.nuclphysb.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

LFV couplings of the extra gauge bosonZand leptonic decay and production of pseudoscalar mesons

Abstract: Considering the constraints of the lepton flavor violating (LFV) processes μ → 3e and τ → 3μ on the LFV couplings Z i j , in the contexts of the E 6 models, the left-right (LR) models, the "alternative" left-right (ALR) models and the 331 models, we investigate the contributions of the extra gauge boson Z to the decay rates of the processes i → j ν ν , τ → μP and P → μe with P = π 0 , η and η . Our numerical results show that the maximal values of the branching ratios for these processes are not dependent on t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The flavor violation (FV) issue has allowed us to relate the hypothetical Z 0 particle with several processes such as single top production [3,4], the D 0 −D 0 mixing system [4], the b 0 q −b 0 q mixing system [16], lepton flavor-violating decays [5,11,17,18], etc. In this way, by using the most general renormalizable Lagrangian that includes FV mediated by a new neutral massive gauge boson, we will estimate the impact of FCNC on the electromagnetic dipole moments of the tau lepton and the chromoelectromagnetic dipole moments of the top quark, resorting to different grand unification models (GUT) with extended current sectors [3,19].…”
Section: Introductionmentioning
confidence: 99%
“…The flavor violation (FV) issue has allowed us to relate the hypothetical Z 0 particle with several processes such as single top production [3,4], the D 0 −D 0 mixing system [4], the b 0 q −b 0 q mixing system [16], lepton flavor-violating decays [5,11,17,18], etc. In this way, by using the most general renormalizable Lagrangian that includes FV mediated by a new neutral massive gauge boson, we will estimate the impact of FCNC on the electromagnetic dipole moments of the tau lepton and the chromoelectromagnetic dipole moments of the top quark, resorting to different grand unification models (GUT) with extended current sectors [3,19].…”
Section: Introductionmentioning
confidence: 99%
“…The flavor violation (FV) issue has allowed us to relate the hypothetical Z ′ particle with several processes such as single top production [3,4], the D 0 − D0 mixing system [4], the b 0 q − b0 q mixing system [16], lepton flavor-violating decays [5,11,17,18], etc. In this way, by using the most general renormalizable Lagrangian that includes FV mediated by a new neutral massive gauge boson, we will estimate the impact of FCNC on the electromagnetic dipole moments of the tau lepton and the chromoelectromagnetic dipole moments of the top quark, resorting to different grand unification models (GUT) with extended current sectors [3,19].…”
Section: Introductionmentioning
confidence: 99%
“…Reference [12] has shown that the most stringent constraints on the LFV coupling constants g µe L,R , g τ e L,R and g τ µ L,R come from the LFV decays µ → 3e, τ → 3e and τ → 3µ, respectively. Reference [13] has given the constraints on the coupling factors g ij L,R for several Z ′ models and further calculated their contributions to the LFV processes P → µe and τ → µP with the pseudoscalar meson…”
mentioning
confidence: 99%